Pattern visual evoked potential in newly diagnosed hypertensive individuals - Achuthan, Anitha; S., Girija (International Journal of Research in Medical Sciences, 2017)
Background: Neuronal dysfunction in hypertension with multifactorial aetiology involves white matter involvement and strongly associated with presence of retinal micro vascular lesions. Cortical lesions associated with optic nerve damage and retinopathy leads to visual disturbances. VEPs are the potential changes recorded from the scalp in response to visual stimuli. Since optic nerve is considered to be the part of brain, its subclinical involvement is likely hypertension. It is in this connection the present study involving visual evoked potential was done to see if there was any change in functional integrity of visual pathways in hypertension. The aim of the study was to evaluate the visual evoked potential in newly diagnosed hypertensive patients who have not taken any antihypertensive drugs before. Methods: 50 cases were selected based on inclusion and exclusion criteria and compared with 50 age, sex matched controls. Study was conducted after getting informed consent, by using the Medicaid polyrite instrument and VEP readings had been taken by standard procedure. Results: Study shows significant P100 latency when analysed through Levene’s test for equality of variances having p100 latencies for right eye 4.19±0.4 with p value of 0.003 and left eye 5.30±0.02 with p value of 0.000 substantiating prechiasmal lesion. Conclusions: Statistically significant delay in p100 suggests that the development of hypertensive retinopathy sub clinically, occurs in very early stages of Hypertension, which is not detectable on routine clinical examination. VEP can be suggested for screening in high-risk individuals to evaluate the functional integrity of visual pathway in hypertension and as a key to unravel the mystery of hidden Hypertensive Morbidity and Mortality.